Conducting Health Research in the Current Afghan Society: Challenges, Opportunities, and Recommendations - Stanikzai MH; Wafa MH; Rahimi BA; Sayam H (Dove Medical Press, 2023)
Muhammad Haroon Stanikzai,1 Mohammad Hashim Wafa,2 Bilal Ahmad Rahimi,3 Hadia Sayam4 1Department of Public Health, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 2Neuropsychiatric and Behavioral Sciences Department, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 3Department of Pediatrics, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 4Para-Clinic Departments, Faculty of Medicine, Malalay Institute of Higher Education, Kandahar, AfghanistanCorrespondence: Muhammad Haroon Stanikzai, Department of Public Health, Faculty of Medicine, Kandahar University, District # 10, Kandahar, 3801, Afghanistan, Tel +93704775578, Email haroonstanikzai1@gmail.comAbstract: Research makes a significant contribution to academic excellence and holds the potential to facilitate societal development. Despite the increasing importance of health research in developing new therapies and galvanizing notable progress in public health, the landscape of health research in Afghanistan remains profoundly deficient. This article reveals that health research in Afghanistan requires significant growth to meet the standards set on regional and global grounds.Keywords: health research, Afghanistan, political instability, challenges, recommendations